MODERN APPROACHES TO VIRTUAL LEARNING ENVIRONMENTS IN DIDACTICS OF PHYSICS - Iryna V. Salnyk (Інформаційні технології і засоби навчання, 2014)
The aim of our research is to identify the factors that influence on the development of modern learning environment and to draw the main lines of the development through interconnected use of virtual and real in teaching process of physics and for later use of them in the development of educational methodical physical experiment. The analysis allowed to distinguish those factors in the development of physical education, which related to its virtualization, which, in our opinion, significantly affect on the formation of new content of each component of educational systems' virtual learning process of physics and allow you to create a new learning environment of physics.